PHYSIOTHERAPY MANAGEMENT OF KNEE OSTHEOARTHRITIS IN ELDERLY: A Case Study - Arizona, Diara; Herawati, Isnaini; Arifin, Akhmad Zainal (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Osteoarthritis (OA) knee is a degenerative and chronic disease of the knee joint due to damage to hyaline cartilage and the most common type of arthritis among individuals over 65 years of age. OA knee is directly related to disability related to physiotherapy problems such as pain, quadriceps dysfunction, and proprioceptive disorders. Therefore, proper management of knee OA is needed to prevent disease progression, reduce pain, and improve knee function in daily functional activities. Case presentation A female patient named MH aged 66 years. The patient had a chief complaint of pain in the right knee. Complaints worsens especially when going up and down stairs and when standing for long periods and walking long distances. The patient also feels stiffness in the knee joint in the morning with a duration of less than 30 minutes. Management and outcomes Giving several optional interventions such as ultrasound, exercise program including static quadriceps exercise, and land base exercise itseffectives for reduce pain, increase muscle strength, increase joint range of motion and improve stability and balance in OA knee. Discussion After being given physiotherapy intervention and exercise programs including static quadruceps exercise and land base exercise, the results were a decrease in motion pain and pressure, and there was an increase in flexor and extensor muscle strength from T1 with a muscle strength value of 4/5 , to 5/5 at T4, There is an increase in the range of motion of the joint at T1the result is 1000 becomes 1300 at T4. and a decrease in risk factors for falls and an increase in balance and stability in the knee joint. Conclusion After physiotherapy intervention in the form of ultrasound and exercise program that includes static quadriceps exercise, land base exercise for 4 therapy sessions can reduce pain levels, increase leg muscle strength, improve balance and reduce the risk of falls and functional activities in the elderly with OA knees.